2015
DOI: 10.1155/2015/843078
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Movement Patterns during Intubation between Novice and Experienced Providers Using Mobile Sensors: A Preliminary, Proof of Concept Study

Abstract: Background. There are likely marked differences in endotracheal intubation (ETI) techniques between novice and experienced providers. We performed a proof of concept study to determine if portable motion technology could identify the motion components of ETI between novice and experienced providers. Methods. We recruited a sample of novice and experienced providers to perform ETIs on a cadaver. Their movements during ETI were recorded with inertial measurement units (IMUs) on the left wrist. The signals were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The energy developed by muscles is transmitted to the patient's airway through the laryngoscope in the form of horizontal and perpendicular forces to expose the glottis. The traditional direct laryngoscopy using the Macintosh laryngoscope blade requires the line-of-sight alignment of the patient's mouth, pharynx, and larynx and adjustment of body posture to gain binocular vision and produce optimal lifting and pushing [2]. The laryngoscope Intubrite is advertised by the manufacturer as a new, ergonomic shape handle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy developed by muscles is transmitted to the patient's airway through the laryngoscope in the form of horizontal and perpendicular forces to expose the glottis. The traditional direct laryngoscopy using the Macintosh laryngoscope blade requires the line-of-sight alignment of the patient's mouth, pharynx, and larynx and adjustment of body posture to gain binocular vision and produce optimal lifting and pushing [2]. The laryngoscope Intubrite is advertised by the manufacturer as a new, ergonomic shape handle.…”
Section: Discussionmentioning
confidence: 99%
“…3. Model badawczy -pomiar aktywności mięśni używanych w trakcie intubacji za pomocą oprogramowania komputerowego i aparatu MyoPlus 2 in the left arm and shoulder [2]. The studied muscles were: biceps brachii, triceps brachii and deltoideus in the left upper limb.…”
Section: Fot 2 Sposób Wykonania Laryngoskopii Bezpośredniejunclassified
“…Literature supports the use of commercial motion sensors as a cost-effective method for kinematic evaluations involving human performance [19], but there are currently only a handful of articles that have described investigations involving motion sensors during intubations [6,[21][22][23][24]. However, to our knowledge, this is the first study that makes use of accelerometry motion sensors as a surrogate for evaluating how endotracheal intubation technique differs when practitioners are placed under experimental conditions.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Other investigators have compared the motion of experienced and novice laryngoscopists. Carlson and colleagues 34 reported that emergency medicine attendings differed from residents and beginners in smoother laryngoscope acceleration, less variability in movement patterns, and greater consis- tency in the angle of the laryngoscope handle. 32 Rahman and colleagues found that laryngoscope angle was a distinguishing feature with experienced anesthetists tilting the laryngoscope farther from vertical than did medical students.…”
Section: Discussionmentioning
confidence: 99%